2019
DOI: 10.1002/andp.201800469
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Transmission in the Planar Chiral Nanostructure Induced by Electric and Magnetic Resonance at the Same Wavelength

Abstract: Asymmetric transmission (AT) reflects the conversion efficiency of a chiral nanostructure for circularly polarized light and is widely used in polarization and optoelectronic devices. In this study, a new mechanism is proposed to generate AT when a planar chiral nanostructure is illuminated under left-handed circularly polarized (LCP) and right-handed circularly polarized (RCP) light illumination. The new mechanism can be achieved by breaking the symmetry of the designed planar chiral nanostructure which give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Rajaei et al experimentally reported giant circular dichroism (CD) with ramp-shaped plasmonic nanostructures [34]. In the above-mentioned works [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], we find that all designs are based on structure-surface-confined field effects to realize a variety of applications while ignoring spatial effects such as neutral atom trapping, an application that requires a noncontact field to be implemented.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Rajaei et al experimentally reported giant circular dichroism (CD) with ramp-shaped plasmonic nanostructures [34]. In the above-mentioned works [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], we find that all designs are based on structure-surface-confined field effects to realize a variety of applications while ignoring spatial effects such as neutral atom trapping, an application that requires a noncontact field to be implemented.…”
Section: Introductionmentioning
confidence: 85%
“…Among them, there is a class of metamaterials with a special structure, named chiral metamaterials, which shows different electromagnetic response, also called chirality, to right-and left-handed circularly polarized (RCP and LCP) light [13][14][15]. This unique optical response renders chiral metamaterials highly promising candidates for a variety of applications [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In general, chiral metamaterials are designed to be single-layered (planar chiral metamaterial) because of the relative ease of their fabrication [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Chirality refers to the fact that a structure cannot overlap with its mirror image; a structure and its mirror image are called enantiomers. , Chirality is ubiquitous in nature, particularly in proteins and DNA and is an integral part of life, attracting the attention of many researchers exploring methods for its detection and for the separation of enantiomers. Chiral materials exhibit novel electromagnetic phenomena, such as circular dichroism (CD), , negative refractive index, and asymmetric transmission effects. , CD is the differential transmission between left-circularly polarized (LCP, −) and right-circularly polarized (RCP, +) light in chiral nanostructures . The CD spectra are often used in characterizing the spatial structures of chiral materials and identifying the chiral characteristics of an unknown chiral material.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral materials exhibit novel electromagnetic phenomena, such as circular dichroism (CD), 3,4 negative refractive index, 5 and asymmetric transmission effects. 6,7 CD is the differential transmission between left-circularly polarized (LCP, −) and right-circularly polarized (RCP, +) light in chiral nanostructures. 1 The CD spectra are often used in characterizing the spatial structures of chiral materials and identifying the chiral characteristics of an unknown chiral material.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Thus, discriminating and detecting different chiral stereoisomers are necessary. Chiral substances usually exhibit special optical activities, such as asymmetric transmission, [5,6] circular dichroism (CD), [7,8] and circular polarization luminescence. [9,10] Optical activity can detect and characterize molecular chirality by the absorption difference of circularly polarized light by chiral stereoisomers.…”
Section: Introductionmentioning
confidence: 99%